Health care services for older people in COVID-19 pandemic times - A Nordic comparison - Trond Bliksvær; Therese Andrews; Andrej Christian Lindholst; Auvo Rauhala; Maria Wolmesjö; Timo S. Sinervo; Lisbeth M. Fagerström; Morten Balle Hansen (Taylor & Francis Group, 2024)
AbstractObjective To explore the Nordic municipal health and care services' ability to promote principal goals within care for older people during the COVID-19 pandemic.Design and setting Two surveys were conducted among managers of municipal health care services for older people in Denmark, Finland, Norway and Sweden; the first around 6 months into the pandemic (survey 1), and the second around 12 months later (survey 2). Data were analysed through descriptive statistics, and multiple regression (OLS).Subjects 1470 (survey 1, 2020) and 745 (survey 2, 2021) managers. 32% in home care, 51% in nursing homes, 17% combined.Results In all countries the pandemic seems to have had more negative impact on eldercare services' ability to promote an active and social life, than on the ability to promote or enhance older people's mental and physical health. The regression analysis indicates that different factors influence the ability to promote these goals. Managers within nursing homes reported reduced ability to promote mental and physical health and an active social life to a significantly lower degree than managers of home care. The effect of three prevention strategies (lock down, testing, and/or organisational change), were explored. Organisational change (reorganize staff and practice, restrict use of substitutes) tended to impact the units' ability to promote a social life in a positive direction, while lock down (areas, buffets etc) tended to impact both the ability to promote mental/physical health and a social life in a negative direction.Conclusion Measures that can improve opportunities for an active and social life during a pandemic should have high priority, particularily within home care.